RNA-binding protein hnRNPR reduces neuronal cholesterol levels by binding to and suppressing HMGCR - John Agbo; Akinsola Raphael Akinyemi; Dingfeng Li; Qingyang Zhang; Xiaohui Li; Wenbo Li; Juan Zhang; Qiang Liu (Journal of Integrative Neuroscience, 2021)
Recent studies have identified multiple RNA-binding proteins tightly associated with lipid and neuronal cholesterol metabolism and cardiovascular disorders. However, the role of heterogeneous nuclear ribonucleoprotein R (hnRNPR) in cholesterol metabolism and homeostasis, whether it has a role in regulating 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR), is largely unknown. This research identifies hnRNPR as a repressor of HMGCR. Knockdown and overexpression of hnRNPR in cultured neuroblastoma cell (N2a) and MN1 cell lines enhances and inhibits HMGCR in vitro, respectively. hnRNPR may exert its repressive activity on HMGCR mRNA and protein levels by using its RNA recognition motif (RRM) in recognizing and modulating the stability of HMGCR transcript. Our RNA immunoprecipitation and luciferase reporter assays demonstrate a direct interaction between hnRNPR and HMGCR mRNA. We also demonstrated that hnRNR binds to the 3′ untranslated region (3′ UTR) of HMGCR and reduces its translation, while hnRNPR silencing increases HMGCR expression and cholesterol levels in MN1 and N2a cells. Overexpression of HMGCR significantly restores the decreased cholesterol levels in hnRNPR administered cells. Taken together, we identify hnRNPR as a novel post-transcriptional regulator of HMGCR expression in neuronal cholesterol homeostasis.